2008
DOI: 10.1186/1743-422x-5-140
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Us3 Gene Deletion Influences Toll-like Receptor Responses in Cultured Monocytic Cells

Abstract: Background: Toll-like receptors have a key role in innate immune response to microbial infection. The toll-like receptor (TLR) family consists of ten identified human TLRs, of which TLR2 and TLR9 have been shown to initiate innate responses to herpes simplex virus type 1 (HSV-1) and TLR3 has been shown to be involved in defence against severe HSV-1 infections of the central nervous system. However, no significant activation of the TLR3 pathways has been observed in wild type HSV-1 infections. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…We have shown previously that the HSV-1 ICP4 and Us3 deletion mutant d120 induces apoptosis in cultured monocytic cells (U937) (Peri et al, 2008). In order to study whether d120 infection also induces other types of cell death, the proportions of viable, apoptotic and necroptotic cells were analysed in HSV-1-infected U937 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown previously that the HSV-1 ICP4 and Us3 deletion mutant d120 induces apoptosis in cultured monocytic cells (U937) (Peri et al, 2008). In order to study whether d120 infection also induces other types of cell death, the proportions of viable, apoptotic and necroptotic cells were analysed in HSV-1-infected U937 cells.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that the ICP4 and Us3 deletion mutant of HSV-1, d120, induced cell death in monocytic cells, mainly because of apoptosis (Peri et al, 2008). In the present study, we have characterized the d120-induced cell death in monocytic cells further, and have studied the roles of cathepsins and caspase 3 in d120-induced cell death.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, Peri et al reported that US3-null HSV-1 induces a strong activation of IRF-3 and type I IFN mRNA expression and that HSV-1 US3 downregulates the intracellular expression of TLR3 and the type I interferon-inducible protein MxA, which is known to posses antiviral activity (171). In addition, HSV-1 US3 phosphorylates the gamma interferon (IFN-␥) receptor, which interferes with IFN-␥-dependent gene expression (120).…”
Section: Herpesvirusesmentioning
confidence: 99%
“…Lastly, Us3 functions as a protein kinase to impede apoptosis thereby promoting viral gene expression (Leopardi et al, 1997). With respect to the type I and II IFN response, Us3 alters TLR3-mediated signalling by decreasing TLR3 mRNA expression, resulting in depleted IRF3 homodimerization (Peri et al, 2008). Additionally, Us3 post-translationally modifies type II IFN receptors via phosphorylation, resulting in decreased expression of IFNγ-dependent genes (Liang & Roizman, 2008).…”
Section: Introductionmentioning
confidence: 99%